Effect of the Independent Acid Base Variables on Anion Gap Variation in Cardiac Surgical Patients: A Stewart-Figge Approach. (3rd February 2014) - Agrafiotis, Michalis; Keklikoglou, Ilias; Papoti, Sofia; Diminikos, George; Diplaris, Konstantinos; Michaelidis, Vassileios
Abstract : Purpose . To determine the effect of each of independent acid base variables on the anion gap (AG) value in cardiac surgical patients. Methods . This retrospective study involved 128 cardiac surgical patients admitted for postoperative care. The variation of AG (A G v a r ) between the day of admission and the first postoperative day was correlated via a multiple linear regression model with the respective variations of the independent acid base variables, that is, apparent strong ion difference (S I D a ), strong ion gap (SIG), carbon dioxide (PCO2 ), and albumin and phosphate concentrations. Results . The variations of all the above variables contributed significantly to the prediction of A G v a r (adjusted R 2 = 0.9999, F = 201890.24, and P < 0.001 ). According to the standardized coefficients ( β ),   S I G v a r ( β = 0.948, P < 0.001 ), [ A l b u m i n ] v a r ( β = 0.260, P < 0.001 ), and [ P h o s p h a t e ] v a r ( β = 0.191, P < 0.001 ) were the major determinants of A G v a r with lesser contributions from S I D a,   v a r ( β = 0.071, P < 0.001 ) and P C O 2,   v a r ( β = −0.067, P < 0.001 ). Conclusions . All the independent acid base variables contribute to the prediction of the AG value. However, albumin and phosphate and SIG variations seem to be the most important predictors, while AG appears to be rather stable with changes in PCO2 and S I D a .